2005
DOI: 10.1021/ci0496494
|View full text |Cite
|
Sign up to set email alerts
|

3D-QSAR and Molecular Mechanics Study for the Differences in the Azole Activity against Yeastlike and Filamentous Fungi and Their Relation to P450DM Inhibition. 1. 3-Substituted-4(3H)-quinazolinones

Abstract: A combination between 3D-QSAR and molecular mechanics (MM)-docking study was used as a tool to detail and model the mechanism of action of 46 antifungal azoles. Two methods of alignment of the ligands were performed: (i) alignment of the main skeleton without substituents and (ii) alignment of a defined substructure. The best model is characterized by q(2) with the values of 0.70 for yeastlike (yeast), 0.66 for filamentous fungi, and 0.70 for the selectivity against filamentous fungi. 3D-QSAR regression maps d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Further studies should be done to check these factors. For instance, one could use residues (not individual atoms) LBE as a descriptor calculated by molecular mechanics or other techniques [61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies should be done to check these factors. For instance, one could use residues (not individual atoms) LBE as a descriptor calculated by molecular mechanics or other techniques [61].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, for some of the chemicals other oxidation positions in CYP2E1 are likely, producing additional metabolites that are important for carcinogenicity differences too; in some cases, as shown in our docking results, there were two different metabolites produced, which have almost equal quantities, in agreement to the experimental data. However, as we demonstrated recently, when the aim is to compare speciesrelated differences and identify the main ligand-receptor interaction, the use of docking conformers is not critical to obtain a sufficient match between 3D-QSAR, docking and LBE results [61]. Further help comes from 3D-QSAR and GRID maps comparison.…”
Section: Discussionmentioning
confidence: 99%
“…5 Indeed, several three-dimensional quantitative structure-activity relationship studies (3D QSAR) have been reported for different datasets of azole derivatives 2,6,[9][10][11][12] however, this strategy afforded models with moderate robustness and local predictive ability only. For instance, Di Santo and co-workers 1 report that their CoMFA model was contradicted by the synthesis and evaluation of novel compounds.…”
Section: Ketoconazole Nystatin Caspofugin Naftifinementioning
confidence: 99%
“…One of the wellestablished and widely used computational techniques in drug design is the quantitative structure-activity relationship (QSAR) method [22][23][24][25][26][27][28], in which the biological profiles of molecules can be derived based on chemical structural information [29][30][31][32][33][34]. Further improvements and developments of this method have led to the generation of the three-dimensional quantitative structure-activity relationship (3D-QSAR) method [35][36][37][38][39]. 3D-QSAR is widely used in drug design to study molecular features related to the improvement of the biological activity of newly designed inhibitors [26,[40][41][42].…”
Section: Introductionmentioning
confidence: 99%